Hubungan Kecerdasan Interpersonal Dengan Hasil Belajar IPAS Siswa Kelas V SD IT Nurul Islam Singkawang - Muhammad Ghafur; Wahyuni Oktavia; Dewi Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between interpersonal intelligence and learning outcomes of fifth grade social studies at the Nurul Islam Integrated Islamic Elementary School, Singkawang. The type of research used is quantitative with a correlation design. The population in this study were all fifth grade students of the Nurul Islam Integrated Islamic Elementary School, Singkawang and the sample in this study used Simple Random Sampling of 30 students. The results of the study show that based on the results of the calculation of the questionnaire, the students' interpersonal intelligence has an average value of 85%, so it can be concluded that the interpersonal intelligence of students in grade V of SD Islam Terpadu Nurul Islam has a very high criterion. Based on the results of the calculation of the results of the students' social studies learning in grade V of SD Islam Terpadu Nurul Islam has an average of 69, so it can be concluded that the students' social studies learning outcomes have a high criterion. Hypothesis testing using Pearson Product Moment correlation obtained signifikan 0.116 > 0.05 , so it can be concluded that there is no relationship between interpersonal intelligence and the results of students' social studies learning in grade V of SD IT Nurul Islam Singkawang